2019
DOI: 10.1128/aac.00889-19
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside Analogs with Antiviral Activity against Yellow Fever Virus

Abstract: Yellow fever virus (YFV) is a human Flavivirus reemerging in parts of the world. While a vaccine is available, large outbreaks have recently occurred in Brazil and certain African countries. Development of an effective antiviral against YFV is crucial, as there is no available effective drug against YFV. We have identified several novel nucleoside analogs with potent antiviral activity against YFV with 50% effective concentration (EC50) values between 0.25 and 1 μM with selectivity indices over 100 in culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
(11 reference statements)
0
13
0
Order By: Relevance
“…Note that our group previously demonstrated that ALS-8112 is also an inhibitor of Nipah virus replication ( 15 ). Finally, 7-deaza-7-fluoro-2′- C -methyladenosine (compound 1), a nucleoside showing anti-yellow fever virus activity, was also evaluated ( 16 , 17 ). Remdesivir (compound 10) ( 18 ) and β- d - N 4 -hydroxycytidine (NHC; compound 17) were used as positive drug controls for these studies ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Note that our group previously demonstrated that ALS-8112 is also an inhibitor of Nipah virus replication ( 15 ). Finally, 7-deaza-7-fluoro-2′- C -methyladenosine (compound 1), a nucleoside showing anti-yellow fever virus activity, was also evaluated ( 16 , 17 ). Remdesivir (compound 10) ( 18 ) and β- d - N 4 -hydroxycytidine (NHC; compound 17) were used as positive drug controls for these studies ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Through in vitro screening of a small library of nucleoside analogues, 2’-methyl-7-deazaadenosine, 2’-methyl-7-fluoro-7-deazaadenosine, and a ProTide of 2’,2”-dichlorouridine were identified as effective inhibitors of YFV replication with EC 50 values in the 0.25–2.1 μM range and no cytotoxicity up to 100 μM. 158 …”
Section: Yellow Fever Virus (Yfv)mentioning
confidence: 99%
“…Currently, the most promising therapeutic agents in early clinical development are nucleoside analogs that inhibit viral RNA-dependent RNA polymerases [54][55][56][57][58]. For example, galidesivir has in vitro and in vivo activity against a broad range of RNA viruses, including Ebola, Marburg and YFV [58,59].…”
Section: Treatment For Yellow Fevermentioning
confidence: 99%
“…Numerous studies have identified other potential antiviral candidates; however, none have entered clinical trials. For example, sofosbuvir, a uridine analog used to treat hepatitis C, has shown antiviral activity against YFV in cell-based assays and rodent infection models [54,57]. Further preclinical development needs to be done for this and other candidates, and their clinical utility to treat YF remains untested.…”
Section: Treatment For Yellow Fevermentioning
confidence: 99%